Analysis of predictive factors for hospitalization outcomes in older patients: the Geriatric Risk Assessment and Care Evaluation (GRACE) study protocol by the Azienda Ospedaliera San Giovanni-Addolorata (AOSGA) and the Italian Society of Hospital and Community Geriatrics (SIGOT) - Lorenzo Palleschi; Andrea Cavalli; Umberto Giuseppe Galasso; Angelo Scuteri; Elena Del Giudice; Moira Ceci; Liliana Mazza; Filippo Luca Fimognari (Geriatric Care, 2025)
Acute care hospitalization for older people is a major issue in terms of mortality, loss of functional independence, and reduced quality of life. The Geriatric Comprehensive Assessment may be crucial in promoting predictive models of hospitalization outcomes, including clinical, functional, and socio-demographic factors. The Geriatric Risk Assessment and Care Evaluation (GRACE) Study, a collaborative effort between the Azienda Ospedaliera San Giovanni Addolorata (AOSGA) and the Italian Society of Hospital and Community Geriatrics, is an observational, retrospective cohort study. It focuses on patients consecutively admitted to the acute geriatric care unit of AOSGA. The primary objective of the GRACE study is to identify factors that may predict in-hospital mortality. Secondary objectives include analyzing factors influencing the length of hospital stay and discharge setting. This paper details the study’s rationale and methodology and provides a brief overview of existing evidence regarding hospitalization outcomes in older adults.